LAPORAN KASUS: TATALAKSANA PASIEN LUKA BAKAR BERAT DENGAN TRAUMA INHALASI DI UNIT PERAWATAN INTENSIF - Aziz, Arif Aminudin; Sobaryati (E-Journal Widya Kesehatan dan Lingkungan, 2020)
Severe burns are burns with an area of > 25% of the body surface area that often require treatment in the Intensive Care Unit (ICU). This is especially so when inhalation trauma is suspected. The diagnosis of inhalation trauma needs to be made immediately to avoid life-threatening airway obstruction. In severe burns, there are physiological changes involving multiple organs. The handling must also involve multidisciplinary disciplines. Coagulopathy occurs immediately after burns, causing a microvascular reaction around the dermis resulting in expansion of the injury. This paper is a literature review for the requirements for intensive care consultant education exams. Case reports were obtained from ICU patients at Hasan Sadikin Hospital. The patient was treated for 5 days on a ventilator then burns treatment until he was in the High Care Unit room. The conclusion is that burns activate a systemic response due to loss of skin barrier, release of vasoactive mediators from the wound and subsequent infection. The result of this process is interstitial edema of organs and soft tissues. This process requires individual resuscitation treatment, depending on the parameters of the individual patient.